The Spanish Queen dictates the fashion: notes by the secretary of Margaret of Austria (1599-1614) - Shapiro Bella Lvovna (Studia Humanitatis, 2021)
The article considers the court culture of Renaissance Spain, which for a long time acted as a model for many royal houses in Europe. The main question is whether Spain’s entry into the initial period of the decline of the Golden Age influenced the state perception in the eyes of foreign representatives. The focus is on the reception of the Spanish court costume. The material for reflection is an interesting source – notes by Luis Cabrera de Córdoba, secretary of Queen Margaret of Austria.